The Effectiveness Of Content Based Instruction In Teaching Speaking Skill For Efl Learners - Rabi'atul Adawiyah (Universitas Hamzanwadi, 2018)
This study aimed at examining the effectiveness of content based instruction method in teaching speaking skills of EFL learners. This research was a pre-experimental research with pre-test and post-test design. It was conducted at the eleventh grade of MA Darul Aitam Jerowaru in the school year 2017-2018. The sample consisted of 27 students selected by cluster random sampling. The data was collected using a speaking test. In addition to diescriptive statistics the collected data were submited to a paired sample t-test. The mean score of post-test (53.62) was higher than that of pre-test (33.48). The result of the paired sample t-test indicated that there was a significant difference in the mean scores between pre-test and post-test, t(df=26) = 77.53 at p .01. Based on the finding, it can be concluded that content based instruction was an effective method to teach speaking.